Structures of Azemiops feae venom phospholipases and cys-rich-secretory protein and implications for taxonomy and toxinology. (May 2016) - Tsai, Inn-Ho; Wang, Ying-Ming; Huang, Kai-Fa
Abstract: The Azemiops snakes are pit-less and phylogenetically located at the Crotalinae and Viperinae divergence. cDNAs encoding five Azemiops venom phospholipase (sPLA2 ) molecules were cloned and sequenced; their signal-peptides were similar to those of crotalid sPLA2 s. Based on their calculated pI-values and residue-49 substitutions, they were designated as Af-E6, Af-N49a, Af-N49a1, Af-N49a2, and Af-N49b, respectively. The first three isoforms, comprising 3–4% of the venom proteins, were purified by reversed-phase HPLC. Af-E6 is catalytically active and has >80% sequence-similarity to other Glu 6 -PLA2 (a pitviper venom-marker). Results of phylogenetic analyses reveal that acidic Af-N49a and Af-N49a1 are rather unique and loosely linked with crotalid PLA2 s, while Af-N49b is related to the viperid PLA2 s with Ser 1 substitution. Notably, the Asn 49 -substitutions in these molecules imply catalytic-independent mechanisms. The 3D-models of Af-E6 and Af-N49a have surface electropotential maps similar to each other and to those of antiplatelet PLA2 s, while the Af-N49b model is similar to basic and myotoxic sPLA2 molecules. From Azemiops feae and four other Viperidae, we cloned five novel Cys-rich secretory proteins (CRISPs). Azemiops CRISP and natriuretic-peptide precursors share more sequence similarities with those of crotalid venoms than with viperid venoms, further supporting the theory that Azemiops are sister taxons to pit vipers, especially Tropedolaemus . Graphical abstract: Highlights: Four acidic and one basic PLA2 s were cloned and three acidic PLA2 s were isolated. Af-E6 is similar to acidic marker-PLA2 of pitviper venom, the N49-PLA2 s are unique. The CRISP of Azemiops is more similar to those of crotaline than those of viperine. Azemiops and Tropidolaemus appear to be related based on their venomics. Abundant neurotoxic and hypotensive peptides are derived from their CNP-precursors.